The effect of Vitamin E on the sciatic nerve lipid peroxi dation in streptozotocin induced diabetes mellitus - Ercel, Ergul; Baydas, Giyasettin; Akyol, Ali; Eksioglu, Emal; Canpolar, Leyl (My University, 1999)
Diabetes mellitus has been induced in rats of the same age group (2 months) through streptozotocin injection of 60 mg/kg to show the effect of the lipid peroxidation on the formation of diabetic neuropathy and the therapeutic contribution of an antioxidant like vitamin E to the treatment of neuropathy. Three groups with ten rats each have been formed, one of the groups being used as a control group. A 10 week insulin therapy was applied to the first group, while the second group received a dose of vitamin E 120 mg/kg intraperitoneally (i.p.) every other day, in addition to the treatment of insulin for a period of 10 weeks. Physiologic serum was applied to the control group. HbA1C and glucose levels in blood samples obtained from the three groups were determined at the end of the study. Malon dialdehyde (MDA) levels which are a measure of the lipid peroxidation (LPO) has been determined in the sciatic nerves removed bilaterally. The sciatic nerve MDA levels of vitamin E administered diabetic rats have been found significantly lower than those in the other diabetic group (p<0.01). No significant differences have been detected in HbA1C amounts of the groups. Electron microscopy showed some abnormalities in sciatic nerve of diabetic rats as compared with the control. These results demonstrated that lipid peroxidation was influential in the development of diabetic neuropathy and the administration of vitamin E prevented lipid peroxidation, subsequently slowing down the development of neuropathy.
Keywords: Diabetes mellitus; Lipid peroxidacion; Neuropathy; Streptozotocin; Vitamin E